Identification of a Heterozygous Mutation in the TGFBI Gene in a Hui-Chinese Family with Corneal Dystrophy - Qin Xiang; Lamei Yuan; Yanna Cao; Hongbo Xu; Yunfeiyang Li; Hao Deng (Journal of Ophthalmology)
Background/Aims. Corneal dystrophies (CDs) belong to a group of hereditary heterogeneous corneal diseases which result in visual impairment due to the progressive accumulation of deposits in different corneal layers. So far, mutations in several genes have been responsible for various CDs. The purpose of this study is to identify gene mutations in a three-generation Hui-Chinese family associated with granular corneal dystrophy type I (GCD1). Methods. A three-generation Hui-Chinese pedigree with GCD1 was recruited for this study. Slit-lamp biomicroscopy, optical coherence tomography, and confocal microscopy were performed to determine the clinical features of available members. Whole exome sequencing was performed on two patients to screen for potential disease-causing variants in the family. Sanger sequencing was used to test the variant in the family members. Results. Clinical examinations demonstrated bilaterally abundant multiple grayish-white opacities in the basal epithelial and superficial stroma layers of corneas of the two patients. Whole exome sequencing revealed that a heterozygous missense mutation (c.1663C > T, p.Arg555Trp) in the transforming growth factor beta-induced gene (TGFBI) was shared by the two patients, and it cosegregated with this disease in the family confirmed by Sanger sequencing. Conclusions. The results suggested that the heterozygous TGFBI c.1663C > T (p.Arg555Trp) mutation was responsible for GCD1 in the Hui-Chinese family, which should be of great help in genetic counseling for this family.